RESEARCH ON ELECTROCHEMICAL METHODS TO REMOVE FLUORIDE FROM WATER - Khue, Vo Anh (Hue University Journal of Science: Natural Science, 2017)
The use of electrochemical methods such as micro-electrolysis, electrocoagulation, and micro-electrolysis combined with electrocoagulation to remove fluoride from water was studied in this paper. The results indicated that the micro-electrolysis (using Fe/C particles) and the electrocoagulation (using iron electrodes) were not suitable for removal of fluoride from water solutions. The electrocoagulation method with aluminum electrodes for the removal of fluoride was very good. But it is not as good as the micro-electrolysis (using Fe/C particles) combined with the electrocoagulation method (using aluminum electrodes). At the optimal condition of the micro-electrolysis (using Fe/C particles) combined with the electrocoagulation method (using aluminum electrodes) and the initial concentration of fluoride ion of 50 mg/L, the removal efficiency of fluoride ion is 94.03% and the residual concentration is 2.986 mg/L.